Social Communication of Transportation: A Bridge Model Connecting Tourism Destination and Psychological Perception - Zhang, Ligang; Wang, Xingrong; Li, Yi; Zhu, Yan; Wei, Feng; Zhao, Shaoqiong (Frontiers in Psychology, 2022)
This article studies the impacts of social communications on transportation routes in the field of tourism and explores the relationship between tourists’ destinations and their psychological perceptions. In terms of links between different tourism destinations in space and time dimensions, our empirical analysis leads to the following conclusions: (1) The behavior of tourist flow is a mediating variable on the links between tourist psychological perceptions and tour routes; (2) Three modes of point-line interaction are presented in the space and time of tourism destinations. (3) The scenic city location, name, and features are important to tourists’ psychological perceptions.